2024
DOI: 10.1111/jdv.19772
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy is unreliable in predicting melanoma mortality for both younger and older patients

Anthony J. Dixon,
Athanassios Kyrgidis,
Howard K. Steinman
et al.

Abstract: BackgroundMelanoma disease patterns vary with patient age.AimTo evaluate sentinel lymph node biopsy (SLNB) in managing melanoma at differing patient ages.MethodsOnline prediction tools were applied to compare SLNB positivity (SLNB+) and survival risk at patient ages 20–80. Tübingen melanoma data were used to determine variations in the hazard ratio of SLNB+ for mortality at different patient ages.ResultsRegardless of tumour thickness, predicted SLNB+ rates were markedly higher than mortality rates for 20‐year‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Our recent research has found that the benefit of SLNB is a particularly poor prognostic indicator for patients under 40 and over 60 years of age [ 57 ].…”
Section: Slnb and Agementioning
confidence: 99%
See 2 more Smart Citations
“…Our recent research has found that the benefit of SLNB is a particularly poor prognostic indicator for patients under 40 and over 60 years of age [ 57 ].…”
Section: Slnb and Agementioning
confidence: 99%
“…It is estimated that only 30 of the 1000 patients would die from their melanoma [ 60 ]. The HR specific to this age group demonstrates that there will be two melanoma-specific deaths in this clinical scenario in SLNB- patients for every death in a SLNB+ patient [ 57 ]. A total of 1000 patients would receive added surgery and 120 patients would be potentially treated with ADT to hopefully prolong life for 10 patients.…”
Section: Slnb and Agementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, sentinel node biopsy has low sensitivity for predicting mortality in individuals over 60 years old. Therefore, regarding the two groups, management can be achieved without SLN biopsy via wide local excision [90].…”
Section: General Clinical-histopathological Aspectsmentioning
confidence: 99%
“…The research presented in this article by Dixon et al 1 tackles a critical issue in the management of melanoma, a type of skin cancer known for its aggressive nature and potential for rapid progression. Melanoma's behaviour and prognosis are notoriously variable, influenced significantly by patient age, among other factors.…”
mentioning
confidence: 99%